Zmiany w składzie chemicznym gleby leśnej i porolnej po wprowadzeniu trocin iglastych na tle przebiegu elementów pogody - Małecka, Monika; Sierota, Zbigniew; Wójcik, Józef (Leśne Prace Badawcze, 2014)
We analysed changes in soil chemical properties (pH, C:N, N, P, K, Ca, Na) inside two forest areas chosen for renewal (Lubartów A and B) and within one post-agricultural site (Świerczyna) designated for afforestation with Scots pine. The experimental plots were located in areas known as persistent cockchafer grub spots. The Lubartów A site was not fenced and showed signs of wild boar activity. Analyses were carried out in the autumn of 2011 and spring 2012, prior to pine sawdust application to the soil and before tree planting, respectively, and again one year later in May 2013. Precipitation as well as air and soil temperatures were recorded throughout the experimental period. We found that soil temperature and humidity, determined by changes in weather, differences in soil chemical properties between forest and agricultural sites as well as sawdust treatments differentially affected soil reaction, C : N ratios and nutrient content. In the unfenced area (Lubartów A), the content of nutrient forms available to plants decreased no more under sawdust treatment than under control conditions. In the remaining areas, sawdust treatment caused an increase or no change in soil concentrations of the investigated nutrients. Under suitable temperature and humidity conditions, sawdust can represent a significant source of energy-rich compounds promoting diversified edaphone activity, which appears to be the main reason for changes in soil nutrient content.